Role of Heme and Heme-Proteins in Trypanosomatid Essential Metabolic Pathways. (2nd March 2011) - Tripodi, Karina E. J.; Menendez Bravo, Simón M.; Cricco, Julia A.
Abstract : Around the world, trypanosomatids are known for being etiological agents of several highly disabling and often fatal diseases like Chagas disease ( Trypanosoma cruzi ), leishmaniasis ( Leishmania spp.), and African trypanosomiasis ( Trypanosoma brucei ). Throughout their life cycle, they must cope with diverse environmental conditions, and the mechanisms involved in these processes are crucial for their survival. In this review, we describe the role of heme in several essential metabolic pathways of these protozoans. Notwithstanding trypanosomatids lack of the complete heme biosynthetic pathway, we focus our discussion in the metabolic role played for important heme-proteins, like cytochromes. Although several genes for different types of cytochromes, involved in mitochondrial respiration, polyunsaturated fatty acid metabolism, and sterol biosynthesis, are annotated at the Tritryp Genome Project, the encoded proteins have not yet been deeply studied. We pointed our attention into relevant aspects of these protein functions that are amenable to be considered for rational design of trypanocidal agents.